Practical experiences of artificial intelligence in science clubs - Ramírez-Montoya, María Soledad; Patiño, Azeneth; Cruz-Sandoval, Marco (Frontiers in Education, 2025)
The 21st century presents us with knowledge and technologies like AI introducing new educational possibilities to improve human talent and performance. In recent years there has been an increase in the literature on artificial intelligence in education and research opportunities with practical experiences in communities in emerging countries. This study investigates how participation in science clubs focused on AI-related projects supports the development of complex thinking and scientific thinking among high school and university students. Drawing on a multiple case study design, the research analyzes six cases involving 83 students across four Mexican cities, all engaged in science clubs jointly organized by academic teams from Mexico and the United States. The results show that (a) participants in all analyzed cases of practical applications of AI demonstrated a high perceived level of complex thinking competency; (b) although no statistically significant differences were found, women, on average, tended to report slightly higher perceptions of complex thinking development compared to their male counterparts; and (c) a similar non-significant trend was observed for scientific thinking, with women reporting marginally higher self-perceived levels than men. These insights contribute to the global conversation on integrating AI into non-formal education to cultivate transversal cognitive skills applicable across diverse educational contexts.